Written Knowledge and its Impact on the Advancement of Society: Kosovo Case - Shala, Jehona (Knygotyra, 2025)
The history of publishing books in Albanian in Kosovo covers the same period as the cultural, educational and political institutionalization of the Albanian society of Kosovo. This parallel development between the book and the institutions made the publishing culture and the institutional culture grow side by side and help mature each other. Therefore, for the Albanian culture in Kosovo, the development and profiling of the book, publishing and publishing houses have a special value because it was only through the book that Kosovo Albanians could be a special cultural and social voice in the Balkan region. Given the importance that the book in Albanian has had for Kosovo Albanians, this article explores the history of Albanian book publishing in Kosovo and its significant impact on the cultural, educational, and institutional development of Albanian society in the region. Despite the lack of a comprehensive understanding of the origins and evolution of Albanian book publishing in Kosovo, this research aims to construct a detailed chronology of its development, including the establishment of the first publishing houses, and to analyse the influence these developments have had on Albanian society. Through the statistical bibliographic method, we will not only recount the history of Albanian book publishing but also uncover insights into the typology of publishing, which has evolved over the decades.